2016
DOI: 10.1142/s2424835516400105
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Trans-osseous Suture of Peripheral Triangular Fibrocartilage Complex Tear

Abstract: The importance of foveal repair of the triangular fibrocartilage complex (TFCC) on stability of the distal radioulnar joint (DRUJ) has been emphasized with increasing knowledge of the anatomy and biomechanics of the TFCC and DRUJ. Although both open and arthroscopic techniques have been described for improving DRUJ stability, there has been a marked evolution of arthroscopic TFCC repair technique with successful clinical outcome. Recently, an arthroscopic trans-osseous technique has been described to repair fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 29 publications
3
18
0
Order By: Relevance
“…26,40,48 Fourteen studies reported peripheral TFCC repairs [26][27][28][29][30][31][32][33][34][35][36][37][38][39] and 13 studies reported foveal avulsions of the TFCC. [40][41][42][43][44][45][46][47][48][49][50][51][52] As the pathoanat-omy of these tears and repair techniques differ, the outcomes of peripheral and foveal tears were analyzed separately.…”
Section: Study and Patient Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…26,40,48 Fourteen studies reported peripheral TFCC repairs [26][27][28][29][30][31][32][33][34][35][36][37][38][39] and 13 studies reported foveal avulsions of the TFCC. [40][41][42][43][44][45][46][47][48][49][50][51][52] As the pathoanat-omy of these tears and repair techniques differ, the outcomes of peripheral and foveal tears were analyzed separately.…”
Section: Study and Patient Characteristicsmentioning
confidence: 99%
“…Seven papers reported a transosseous repair technique. 40,[44][45][46][50][51][52] Iwasaki et al performed arthroscopicassisted transosseous repair using a guiding device through the four to five portal, targeting the fovea. An outside-in technique for the suture shuttle was then utilized, with the sutures finally tied onto the ulnar periosteum over the proximal entrance of the osseous tunnel.…”
Section: Transosseous Foveal Repair (N ¼ 143 Patients)mentioning
confidence: 99%
See 3 more Smart Citations